Classroom Assesment Pada Perkembangan Keaksaraan Anak Usia Dini Melalui Media Flash Card - Malikatus Sholihah; Zulfatin Ni’mah (Alzam: Journal of Islamic Early Childhood Education, 2025)
This study aims to enhance the gross motor development of children aged 5-6 years at RA Hidayatus Sholihin Merakurak through the implementation of the traditional game Ceu Cat. The research sample consisted of 18 students, comprising 10 boys and 8 girls. The study employed a classroom action research approach using the Kemmis and McTaggart model, which includes four stages: planning, action, observation, and reflection. Data were collected through direct observation and documentation of children's activities, then analyzed descriptively and analytically to identify changes in gross motor skills. The research findings indicate that the traditional game method Ceu Cat significantly improved children's gross motor skills over two cycles, with most children reaching the category of development as expected (BSH). These findings affirm that traditional games not only provide enjoyment but also play a crucial role in supporting children's physical development. The conclusion of this study is that the use of the traditional game Ceu Cat is an effective strategy for developing early childhood gross motor skills while simultaneously preserving local cultural heritage in the educational context.